Seawater carbonate chemistry and growth rate, dissolved silicate (DSi) uptake, biogenic silica (BSi) production, and maximum effective quantum yield in five species - Aaron Ferderer; Kai Georg Schulz; Anusuya Willis; Kirralee G Baker; Zanna Chase; Lennart Thomas Bach (PANGAEA, 2025)
This study aimed to map the fitness of ecologically important marine diatoms across a comprehensive matrix of carbonate chemistry con ditions. Fitness landscapes used here encompassed past, present, and future ocean conditions including those expected under OA and OAE. Fitness landscapes were mapped over 11 levels of total alkalinity (2000 to 3350 μmol/kg) and 8 levels of dissolved inor ganic carbon (DIC) (1800 to 3666.67 μmol/kg), for a minimum of 67 treatments per species. Using this matrix, we assessed the growth rate, dissolved silicate (DSi) uptake, biogenic silica (BSi) production, and maximum effective quantum yield in five species of locally iso lated marine diatoms. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from IMAS Metadata Catalogue (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-25.